Prediagnostic Clinical Presentations and Abnormal Laboratory Reports in Patients of Colorectal Carcinoma: A 5 years’ Experience from a Tertiary Care Hospital of Bangladesh - Hossain, Md Shakhawat; Maknunnahar; Anwar, Md Mahfuj Ul; Alam, Khondoker Monirul; Lucky, Jahan Afroza; Ali, Md Naushad; Alam, Md Makhsudul; Jahan, Shah Md Sarwer; Salam, Farhana (Bangladesh Journal of Medicine, 2025)
Background: Colorectal cancer (CRC) comprises a major public health issue globally. Understanding pre-diagnostic clinical features and abnormal laboratory reports in patients with Colo-rectal cancer could enlighten a way of opportunity for earlier diagnosis. This study was aimed to provide the pattern of relevant symptoms and abnormal laboratory results in patients with colorectal cancer before diagnosis. Methods: This cross sectional study held at department of gastroenterology of Rangpur medical College, Rangpur, Bangladesh from January 2019 to December 2023 over a 5 years period. Colonoscopy and histopathologically proven 1150 CRC patients were taken as study subjects. Results: Among the study subjects 73.47% (845) were male and 26.52% (305) were female. In the time before diagnosis of CRC, the most commonly observed symptom was abdominal pain 77.39%, (890) followed by altered bowel habit 46.95%, (540) among this study subjects. Other notable clinical features are Per rectal bleeding 20.69 % (238), abdominal lump17.21% (198), Anemia/pallor 29.56 % (340) and weight loss in 23.21% (267). Laboratory reports of the patients before diagnosis were decreased hemoglobin in 47.04% (541) and high CRP in 65.56 % (754) and high ESR in 51.22%(589) patients. Stool examination shows RBC in 10.78 % (124) cases only. Ultrasonogram shows abdominal lump in 22.96% cases and SOL in liver in 12%. Plain X Ray abdomen shows acute and sub-acute intestinal obstruction in 11.30% cases. 217 (18.86%) patients presented within 6 months of symptom onset and 585 (50.86%) presented between 6 months to 02 years duration. About 35% of patients visited three or more physicians before diagnosis and rest (65%) of the study subjects consulted up to two physicians visit. Conclusion: From this study, it is evident that, if we will be aware of the CRC suggestive symptoms and laboratory reports, there is chance to promote referral for confirm diagnosis. Bangladesh J Medicine 2025; 36(2): 115-122